Transformações políticas e indígenas : movimento e prefeitura no alto rio Negro - Iubel, Aline Fonseca (Universidade Federal de São Carlos, 2015)
This PhD thesis is an ethnography of policies made by the Indians in the Upper Rio Negro in two main areas: the indigenous movement and the Government’s municipality of São Gabriel da Cachoeira, Amazonas State, Brazil. The indigenous organized movement exists in the region since at least the 1970s. However, the debates about political parties politics and attempts to indigenous alliances aiming to hold office in the county, they have intensified only over the years 1990. In both cases some indigenous leaders took ahead the process with a certain way of speech and work, who often expressed the movement as a kind of "laboratory" for partisan politics. That is, there are so many points of intersection of these two spheres which cannot let us think of them as separated or independent in that context. On the other way round, the descriptions and analyzes of some narratives and political events of the upper Rio Negro that are presented in this work show how in these spaces the Indians dialogue, debate, fight and dispute among themselves, but also with two other key players: White people and State. In this sense, the thesis also reflects on the political processes of establishing an indigenous sociality from the state, when, in 2008, there were elected two Indians for mayor and vice-mayor positions in São Gabriel da Cachoeira. The plots, narratives, actions and evaluations of these processes underlie an argument in which the strongest language is on the transformation, instability and reversibility.
Keywords: Política indígena; Movimento indígena; Política partidária; Etnologia indígena; Antropologia política; Indigenous mouvments; Partisan policies; Transformations; Upper rio Negro; CIENCIAS HUMANAS::ANTROPOLOGIA